Soaring Marriage Dispensation Due To Changes In Marriage Age Limit - Wahyuni Kiayi (Estudiante Law Journal, 2026)
The purpose of this paper is to find out the effect of the soaring marriage dispensation after the change in the marriage age limit after Law No. 16 the Year 2019, as well as what are the other factors of the supporter of the soaring application for marriage dispensation after the   Act said.  This author uses an empirical type of writing.  The results of the authors show that the revision of Act Number 1 of 1974 to Act Number 16 Of 2019 Marriage changing the minimum   age limit for marriage greatly affects the application for marriage dispensation, namely the increase in cases of marriage dispensation due to changes in the marriage age limit. The influence of Acthe t resulted in a significant increase in the number of cases due to the influence of an increase in the age rate, ignorance and lack of public knowledge,s well as a lack of socialization from the authorities to the change. As for the supporting factors for the increase in marriage compensation,  name the injury factor,   The outbreak of the Covid-19 pandemic and parents' concerns about pr, promiscuity, and promiscuity.